2021
DOI: 10.1093/ageing/afab200
|View full text |Cite
|
Sign up to set email alerts
|

Utility of white matter disease and atrophy on routinely acquired brain imaging for prediction of long-term delirium risk: population-based cohort study

Abstract: Background brain imaging done as part of standard care may have clinical utility beyond its immediate indication. Using delirium as an exemplar, we determined the predictive value of baseline brain imaging variables [white matter changes (WMC) and atrophy] for delirium risk on long-term follow-up after transient ischemic attack (TIA)/stroke in a population-based cohort study. Methods surviving TIA/stroke participants in the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Future studies should further assess the prognostic utility of CT-derived neuroimaging measures for predicting clinical, cognitive, and functional outcomes in acutely unwell patient populations, such as patients with stroke and delirium. 37,38 Once the prognostic utility of clinical CT scans has been established more firmly, data from acute CT neuroimaging could be incorporated into clinical risk prediction algorithms for post-stroke outcome, particularly should automated quantitative assessment methods become widely clinically available for CT. Such algorithms would facilitate identification of individual patients at risk of poor cognitive and functional outcomes post-stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should further assess the prognostic utility of CT-derived neuroimaging measures for predicting clinical, cognitive, and functional outcomes in acutely unwell patient populations, such as patients with stroke and delirium. 37,38 Once the prognostic utility of clinical CT scans has been established more firmly, data from acute CT neuroimaging could be incorporated into clinical risk prediction algorithms for post-stroke outcome, particularly should automated quantitative assessment methods become widely clinically available for CT. Such algorithms would facilitate identification of individual patients at risk of poor cognitive and functional outcomes post-stroke.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is important given that CT is commonly acquired in clinical practice and is often the only imaging modality available in underserved and under-resourced global regions (Frija et al, 2021). Future studies should assess the prognostic utility of CT-derived imaging measures for predicting other clinical, cognitive, and functional outcomes post stroke (Pendlebury et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating CS-PVS into delirium prediction algorithms might have potential clinical utility in aiding delirium risk stratification, and this needs to be confirmed by future studies. Although a few studies have investigated brain CSVD markers (e.g., WMH and cerebral microbleeds) in relation to delirium (Omiya et al, 2015;Nitchingham et al, 2018;Lachmann et al, 2019;Clancy et al, 2021;Pendlebury et al, 2022), no previous study has yet explored the link between MRI-visible PVS and delirium. PVS is frequently seen in the aging brain (Bown et al, 2022) and has been proposed as a key contributor to cognitive decline and dementia in older adults (Debette et al, 2019;Paradise et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of neuroimaging particularly magnetic resonance imaging (MRI) provides a unique chance to study the neural substrates of delirium, and certain abnormalities on brain MRI have been reported to be associated with delirium ( Nitchingham et al, 2018 ; Kalvas and Monroe, 2019 ). Several studies have indicated that white matter hyperintensities, markers of cerebral small vessel disease (CSVD), can predict the occurrence of delirium ( Omiya et al, 2015 ; Nitchingham et al, 2018 ; Clancy et al, 2021 ; Pendlebury et al, 2022 ). Nevertheless, for other CSVD markers, especially MRI-visible perivascular spaces (PVS), this is still unknown.…”
Section: Introductionmentioning
confidence: 99%